Sebuah Pengujian Pasar Modal yang Efisiensi Pada Bursa Efek Indonesia - Lusianus Heronimus Sinyo Kelen; Alliny Namilana Rambu Hutar (Universitas Kristen Wira Wacana Sumba, 2016)
The development of investment in Indonesia increased rapidly, so it needs to do research related to investment in Indonesia, so it can be useful for decision makers both from the investor (financial community) and the company. Efficient capital market is one of the interesting financial topics to be studied, especially investors and companies desperately need it for better and more informed decision making. In Indonesia alone, research on the efficiency of the capital market has been done is still simple or not robustness. So this study aims to test the form of capital market efficiency in Indonesia.Using a sample of 34 firms and using autocorrelation regression techniques, the results show that capital markets in Indonesia are efficient (weak form), this is indicated by the absence of a relationship between stock prices within the firm. Keywords: Investment, Investor, Company, and Capital Market Efficiency